The comparative accuracy of handprints and footprints for stature and sex determination - Sara Gamal Abbas; Amany Elsayed Abdelrahman; Omneya Saad El-Oefy (Forensic Science International: Synergy)
One of the main goals of forensic medicine is the successful identification of unidentified bodies. This is essential in mass disasters, criminal medicolegal investigations, and most cases of deaths with poorly preserved remains. This study aimed to assess the accuracy of anthropometric determination of handprint versus footprint dimensions for sex and stature estimation in a sample of the Egyptian population and to formulate equations for stature and sex determination using hand and footprint anthropometric measures. A total of two hundred adults, aged 21–40 years, of Egyptian descent were selected for the study. Stature, hand, and footprint dimensions were measured and analyzed. The current study revealed that hand and footprint lengths were the most significant estimators of stature for both sexes. However, footprint measures were significantly better for stature estimation than handprint measures in females, while handprint measures were statistically better estimators of stature than footprint measures in males. On the other hand, the most sexually dimorphic parameters were handprint length, handbreadth, T4, and T5. Importantly, hand parameters were better predictors of sex than foot parameters. In conclusion, footprint measurements were more accurate for estimating stature in females, while handprint measurements were more accurate for males. Additionally, handprint parameters were more effective for sex determination than footprint parameters. Regression equations were presented in this study to estimate the sex and stature of individuals of Egyptian descent from various hand and footprint dimensions.